Quality of life o folder adults: Evaluation in asylum casa hogar la paz (Jóvenes en la Ciencia, 2024)
The world's population ages progressively, needing to know the needs of older people to improve their quality of life levels, especially through physical exercise. Currently, the levels of these are unknown, therefore, the objective of this research was to evaluate the quality of life of older adults in the “La Paz” home, located in Irapuato Gto. A sample population of 22 older adults was taken, including men and women, all of them in the age range of 60-91 years already mentioned, to whom the Coop Wonka questionnaire was applied, used to measure the quality of life related to with health. It was shown that there is 54% of regular quality of life in the total sample and the rest of the percentage with a poor quality of life yielding 46%, taking into account that the sample consists of 59% women and 41% men. These results suggest that older adults in the home perceive a regular quality of life, due to poor social ties or poor quality of relationships with their family members in addition to their state of mind.